Design and Manufacturing of Spinner Machine Using Speed Control - Romiyadi Romiyadi (LP2M - Institut Teknologi Padang, 2018)
The spinner machine was a machine used to reduce the oil content in the foods like chips and can improve the quality of the food to be durable. The purpose of the study was to design and manufacture of spinner machine with a capacity of 4 kg. In this study, the spinner machine was designed and manufactured with a speed control. From the process of designing and manufacturing, has produced a spinner machine with a capacity of 4 kg for a process. The machine uses a electric motor with a power of 0.25 HP.